2000
DOI: 10.1108/10222529200000011
|View full text |Cite
|
Sign up to set email alerts
|

Organisational problems in respect of the implementation of activity‐based costing in South Africa

Abstract: In this study the extent and nature of organisational problems that are encountered in South Africa in respect of the implementation of activitybased costing are examined and compared with difficulties experienced by companies in the British Isles, United States of America and Australia. The investigation comprised a literature survey as well as an empirical study of the companies listed in South Africa.Contrary to the findings of overseas studies, South African companies experience less difficulty in respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…Given that listed companies in Gauteng constitute 51% of all listed companies in South Africa, it is reasonable to infer that this rate is applicable to all listed companies within South Africa. These results are consistent with those obtained by Wessels (1999), who observed that only 15.18% of listed companies in South Africa have attempted to implement ABC. However, these findings contradict the results obtained by Jacobs (2005), which indicated that the adoption rate of ABC in South Africa listed companies was 32%.…”
Section: The Extent Of Abc Diffusion In South Africasupporting
confidence: 92%
“…Given that listed companies in Gauteng constitute 51% of all listed companies in South Africa, it is reasonable to infer that this rate is applicable to all listed companies within South Africa. These results are consistent with those obtained by Wessels (1999), who observed that only 15.18% of listed companies in South Africa have attempted to implement ABC. However, these findings contradict the results obtained by Jacobs (2005), which indicated that the adoption rate of ABC in South Africa listed companies was 32%.…”
Section: The Extent Of Abc Diffusion In South Africasupporting
confidence: 92%
“…Pierce and Brown (2006) found in their study that there was a significant relationship between the success of ABC/M systems and performance evaluation/rewards and adequacy of training. The latter was also found among Jordanian firms (Nassar et al, 2009) and indeed confirmed in a study from South Africa by Wessels and Shotter (2000) where there was a lack of management support. As found in a case study of a bank by Soin et al (2002), an ABC project should not be about more "correct" cost allocation but it should create a new understanding of products, competitors and customers.…”
Section: Methodssupporting
confidence: 64%